Assessment of physical health and physical fitness of students of technical specialties of I course - Korol, S. A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : identification and assessment of levels of physical health and physical fitness of first-year students of the main group. Material : in the experiment participated 264 students (132 boys and 132 girls). The methods of evaluation: physical health by G.L. Apanasenko and physical preparedness for T. Yu. Krutsevich. Results : It was found that more than 75% of the students are low and lower-middle level of physical health. Revealed a level of physical fitness freshmen. 84.8% of boys and 81.1% girls have an average level of physical fitness. This corresponds to a satisfactory evaluation. Found that almost all the students are at risk of development of somatic diseases. Conclusions : These results confirm the tendency to deterioration of health and physical fitness of young people. This requires the development of a program of physical education with an emphasis on improving orientation.